Medical support system (MSS) for ward round using Pocket PC / Mohd Khairul Azmi Hassan - Azmi Hassan, Mohd Khairul (2005)
The usage of computer devices varies throughout the medical field, from the registration desk up to the medical ward. Handheld devices such as Pocket PC are portable and easy to use, thus are suitable tools to be implemented in this area. The objective of the project is to provide an alternative for doctors to use Pocket PCs as oppose to the wireless notebooks that are presently used for ward rounds. The systems and databases are developed based on two platforms; Windows ME on the desktop computer and Windows CE on the Pocket PC. The systems and databases that are developed in the two platforms are then synchronized in the MSS System. An extension of the MSS System is a prototype of an intelligent pharmaceutical prescription system. The system can be used to alert doctors of any incorrect prescription.